Approach to the Fourth Five Year Plan - Planning Commission (Planning Commission, 1968)
The Constitution lays down general directives for economic and social policy of the State, and successive Plans have elaborated the aims and objectives of planned development. A strategy of Indian planning has evolved during the three Five Year Plans. The Fourth Five Year Plan is being framed in the light of all these. However, from time to time situations change and new problems arise. Each five year plan has to take into account its particular context and try to make the required adjustments. This is specially the case with the Fourth Five Year Plan which is being framed after a period of three annual Plans.
Issued on Behalf of Planning Commission Government of India